Correlation between Number of Spot with Body Length in Humback Grouper, Cromileptes altivelis - Y. Yahyadi; R.S. Aliah; M. Murdjani; K. Sumantadinata (Jurnal Akuakultur Indonesia, 2004)
The study with the objective to identify correlation between the number of black spots (dot) and total length was conducted in the humpback grouper. The spots were counted from 423 samples offish which ranged from 1.2 cm to 53.0 cm in size. The numbers of spots were observed at the body, head and fins. The simple linier regression was used to analyze correlation between the number of spots and total length. The regression between total spots (Yi) and total length (X) is Yi = 16.386 X + 80.754; the total spots of the body (Y2) and total length is Y2= 4.230 X + 1.548; the spots of the head (Y3) and total length is Y3 = 3.907 X + 31.728, and the total spots of the fins (Y4) and total length is Y4 = 5.066 X + 42.802. In general, there was a positive correlation between number of black spot and total length. A duplication like mitotic division. The process of black spots duplication probably similar to mitotic division of cell. Key words : Grouper, Cromileptes altivelis, spot (dot), body lenth   ABSTRAK Penelitian bertujuan untuk mengidentifikasi korelasi antara jumlah totol hitam pada ikan kerapu bebek dengan pertambahan panjang tubuhnya. Pengamatan totol dilakukan terhadap 423 ekor kerapu bebek yang berukuran panjang total 1,2 cm sampai 53,0 cm yang diperoleh dari Balai Budidaya Air Payau (BBAP) Situbondo, Jawa Timur. Jumlah totol dihitung pada bagian badan, kepala dan sirip. Data dianaiisis dengan menggunakan regresi linier sederhana. Persamaan regresi linier keseluruhan jumlah totol (Y|) dengan panjang total (X) adalah Y, = 16.386 X + 80.754, jumlah totol pada badan dengan panjang badan Y2 = 4.230 X + 1.548, jumlah totol pada kepala (Y3) dengan panjang badan adalah Y3 = 3.907 X + 31.728, dan jumlah totol pada sirip (Y4) dengan panjang badan adalah Y4 = 5.066 X + 42.802. Secara umum ada korelasi positif antara jumlah totol dengan panjang total. Proses pertambahan jumlah totol diduga seperti pada proses perbanyakan sel secara mitosis. Kata kunci : Ikan kerapu, Cromileptes altivelis, totol, panjang tubuh